2020
DOI: 10.3390/ijms21239179
|View full text |Cite
|
Sign up to set email alerts
|

IP3R Channels in Male Reproduction

Abstract: As a second messenger in cellular signal transduction, calcium signaling extensively participates in various physiological activities, including spermatogenesis and the regulation of sperm function. Abnormal calcium signaling is highly correlated with male infertility. Calcium signaling is mainly regulated by both extracellular calcium influx and the release of calcium stores. Inositol 1,4,5-trisphosphate receptor (IP3R) is a widely expressed channel for calcium stores. After being activated by inositol 1,4,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…It has been documented that sperm ion channels including Ca 2+ play significant regulatory roles in the process of spermatogenesis, controlling sperm maturity and motility, the acrosome response, and fertilization 17 , 52 . These Ca 2+ ions are accumulated in spermatogenic cells at different developmental stages and manage the spermatogenesis and spermiogenesis processes 53 . Therefore, irregular Ca 2+ signaling pathways can impair testosterone levels, which leads to unnatural spermatogenesis and even complete male infertility Furthermore, several reports have shown that the calcium pathway could be interconnected with the apoptosis pathway 26 , 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that sperm ion channels including Ca 2+ play significant regulatory roles in the process of spermatogenesis, controlling sperm maturity and motility, the acrosome response, and fertilization 17 , 52 . These Ca 2+ ions are accumulated in spermatogenic cells at different developmental stages and manage the spermatogenesis and spermiogenesis processes 53 . Therefore, irregular Ca 2+ signaling pathways can impair testosterone levels, which leads to unnatural spermatogenesis and even complete male infertility Furthermore, several reports have shown that the calcium pathway could be interconnected with the apoptosis pathway 26 , 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The GO analysis based on AS data indicated that Sugp2 may participate in metal ion and energy metabolism. Combined with the results of KEGG, Sugp2 may be involved in calcium transport and signal transduction, which play an essential role in male germ cell development and function ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 92%
“…Bitter tastants, including progesterone or chemokines, which can be secreted by the cumulus–oocyte complex, could potentially activate TAS2Rs in sperm. This activation could trigger the release of calcium from internal stores, (Correia et al, 2015; Zhang et al, 2020) resulting in an increase in [Ca 2+ ] i , which in turn could enhance sperm flagellar beating and hyperactivation. Given that cation channel of sperm (CatSper) is a dominant Ca 2+ channel for sperm activation (Hwang & Chung, 2023; Ren et al, 2001), it is plausible that the activation of TAS2Rs could functionally couple with CatSper.…”
Section: The Roles Of Tas2rs In the Male Reproductive Systemmentioning
confidence: 99%